AhR regulates the expression of human cytochrome P450 1A1 (CYP1A1) by recruiting Sp1. (25th June 2019) - Ye, Wenchu; Chen, Ruohong; Chen, Xiaoxuan; Huang, Boyan; Lin, Ruqin; Xie, Xuan; Chen, Jiongjie; Jiang, Jun; Deng, Yiqun; Wen, Jikai
Abstract : Cytochrome P450 1A1 (CYP1A1) is abundant in the kidney, liver, and intestine and is involved in the phase I metabolism of numerous endogenous and exogenous compounds. Therefore, exploring the regulatory mechanism of its basal expression in humans is particularly important to understand the bioactivation of several procarcinogens to their carcinogenic derivatives. Site‐specific mutagenesis and deletion of the transcription factor binding site determined the core cis ‐acting elements in the human CYP1A1 proximal and distal promoter regions. The proximal promoter region [overlapping xenobiotic‐responsive element (XRE) and GC box sequences] determined the basal expression of CYP1A1 . In human hepatocellular carcinoma cells (HepG2) with aryl hydrocarbon receptor (AhR) or specificity protein 1 (Sp1) knockdown, we confirmed that AhR and Sp1 are involved in basal CYP1A1 expression. In HepG2 cells overexpressing either AhR or Sp1, AhR determined the proximal transactivation of basal CYP1A1 expression. Via DNA affinity precipitation assays and ChIP, we found that AhR bound to the promoter and recruited Sp1 to transactivate CYP1A1 expression. The coordinated interaction between Sp1 and AhR was identified to be DNA mediated. Our work revealed a basal regulatory mechanism of an interesting human gene by which AhR interacts with Sp1 through DNA and recruits Sp1 to regulate basal CYP1A1 expression. Abstract : CYP1A1 is an enzyme involved in phase I metabolism within the kidney, liver and intestine. Previous studies identified a role for CYP1A1 in prostate and breast cancer in addition to liver disease, highlighting the need to determine how its basal expression is regulated. Here, Jikai Wen and colleagues report that transcriptional regulation of CYP1A1 is achieved through a DNA‐dependent coordinated interaction between two transcription factors, Sp1 and AhR, which occurs at the overlapping XRE/GC box in the proximal promoter region of the gene. They provide evidence that AhR binds first and then recruits Sp1, shedding light on the regulatory mechanism.